PEMBUATAN SELAI CAMPURAN BUAH PEPAYA DAN BUAH TERUNG BELANDA - Pandiangan, Andreas; Hamzah, Faizah; Rahmayuni, Rahmayuni (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The research aimed were to get the best jam from papaya fruit pulp and tamrillo fruit pulp. The experiment research used Completely Randomized Design (CRD), with 5 treatments as follows: PT1 (80% papaya pulp and 20% tamarillo pulp), PT2 (65% papaya pulp and 35% tamarillo pulp), PT3 (50% papaya pulp and 50% tamarillo pulp), PT4 (35% papaya pulp and 65% tamarillo pulp), and PT5 (20% papaya pulp and 80% tamarillo pulp). The data obtained were analyzed statistically using ANOVA and DNMRT at 5% level. The best treatment jam of this resarch was the jam from treatment of PT5 (20% papaya pulp and 80% tamarillo pulp). The best treatment has moisture content 21.22%, ash content 0.26%, total dissolved solids content 65.33%, fiber content 2.44% and acidity level 3.80%, assessment of sensory test of the best treatment jam very red color, very flavorful tamarillo fruit, slightly sour sweet taste, soft texture and overall assessment of jam favored by panelist.Â Keywords: Jam, papaya and tamarillo.